EMOTIVE CONCEPT IN A LITERARY WORK - Larissa G. Khoreva (Russian Studies in Culture and Society)
The relevance of the article deals with the importance of studying of human emotions in the process of communication. In recent decades the interest of scientists in the emotive field of humanitarian knowledge has significantly increased. The emotional competence and emotional intellect of representatives of modern society, the search for emotional meanings, the role of emoticians in intercultural communication are the subject of their interest.